The Application of The Teaching Contextual Learning (CTL) to Increase The Motivation to Study Primary School Student - Zahrah, Riza Fatimah; Suryana, Yusuf; Enok, Enok (International Conference on Elementary Education, 2020)
The background of research is research results in 2013 that motivation students in resolving word problems mathematics was weak . The purpose of this study is to find a the motivation to study students in resolving word problems mathematics by applying contextual teaching learning ( CTL ). This research was conducted at a grade school in Kuningan districts .The methodology is descriptive , with the quantitative approach and design research used is non-equivalent control group design .This research result indicates the 75 % attention , relevance 71.43 % , confidence 72.22 % and satisfaction 80.07 % that averaged the motivation to study students were % 74.68 .The motivation to study can rise as strategy applied is learning in kinds style, assigned tasks age related and interest, and the emergence of learning community